Designing the housing market for 2030 - a foresight and econometric approach - Jo\~ao Marques; Miguel Viegas; Monique Borges; Eduardo Anselmo (European Regional Science Association (ERSA), 2013)
The paper presents a foresight analysis methodology and its empirical application in the context of housing market. This work was developed in the context of a wider research project, ?Drivers Of housiNg demand in Portuguese Urban sysTem? ? DONUT, which analyses the Portuguese housing market. Decision making models were developed, combining technically informed subjectivity (foresight analysis) with more rigorous models (econometric models). The final outcome of this exercise is the estimation of housing characteristics and its hedonic prices in 2030, i.e., a picture of the housing market in 2030 is built. The importance of the housing sector requires a significant effort to understand its dynamics and analyze the main drivers of the housing market. The social and economic phenomena, as well as the heterogeneity of both housing (prices and features) and consumers are important elements not always included in the analytical models commonly used. The territory structure and the lack of information and transparency of the housing market mechanisms also influence its understanding. There is a variety of literature in the field of spatial economy that works as a theoretical basis for the estimation of hedonic housing prices. However, these analytical models fail on their inability to integrate the variability of exogenous factors. Forecasts on subject affects by high volatility and uncertainty require particular approaches such as foresight analysis which will be the main focus of this paper. In short, a methodology of foresight exercise is presented, discussing the combination of two techniques: scenario analysis and Delphi surveys. This methodology is supported on the assumption that it is possible: i) to discuss strategies in the context of great uncertainty; and ii) to identify trends and assess future evolution. In addition, the most relevant results of this exercise will be analyzed and presented, contributing to the definition of important guidelines for real estate agents. The work is structured in 4 parts: i) framework of the foresight exercise; ii) brief description of the exogenous housing market context (scenario analysis), iii) definition of the characteristics that describe the standard houses and their distribution in space, and iv) valuation of the standard houses previously identified.
Keywords: C53; R31; 330